Astma oskrzelowa i jej wyzwalacze: opis przypadku we wschodniej Słowacji - Harvanová, Gabriela; Durankova, Silvia; Csanady, Alexander; Rosoľanková, Ľubov; Majherová, Mária (Alergologia Polska - Polish Journal of Allergology, 2022)
The aim of study was to elaborate the basic theoretical knowledge regarding the respiratory system, in order to further characterize bronchial asthma, its symptoms, diagnosis, risk triggers, and inhibitors based on the available professional and international literature. We established several hypotheses, which we subsequently either confirmed or rejected. The research was carried out in the territory of eastern Slovakia, specifically in the immunoallergological outpatient clinic, which provided us with the necessary information. Based on the processed data, we can conclude that there is a significant association between gender and patients’ control of inhalation technique. According to the literature, allergens are considered to be among the most common asthma triggers, which was confirmed by our research. We found that patients have the greatest difficulties in the spring and autumn seasons, when there is not only a large amount of pollen in the air, but also an increased incidence of infectious and viral diseases.